Three-dimensional echocardiography in transcatheter edge-to-edge tricuspid valve repair. (14th October 2021) - Orban, M; Wolff, S; Stolz, L; Braun, D; Stark, K; Mehr, M; Stocker, T; Orban, M; Hagl, C; Massberg, S; Nabauer, M; Hausleiter, J
Abstract: Background: Transcatheter tricuspid valve repair (TTVR) is a new treatment option for severe tricuspid regurgitation (TR). First reports have reported conflicting results on development of right ventricular (RV) function after TTVR and questioned the role of conventional echocardiographic parameters to predict outcome. Purpose: The aim of this study was to evaluate 3D echocardiography for the comprehensive assessment of RV function and its prognostic value for TTVR-treated patients. Methods: We included patients undergoing TTVR from February 2017 to July 2019 who had preprocedural 3D assessment of RV volumes and ejection fraction. At follow-up (FU), 3D echo was performed to evaluate right ventricular reverse remodeling. All-cause mortality was assessed as clinical endpoint. Results: 75 patients treated with TTVR for isolated, severe TR had 3D echo assessment. TTVR reduced TR from grade ≥3+ to ≤2+ in 83.1% of patients at discharge. 3D-RV end-diastolic volume (−46.3 ml, p<0.001), end-systolic volume (−22.0 ml, p=0.027) and 3D-RV ejection fraction (−4.7%, p<0.001) decreased at short-term FU at 1-month and remained stable at 6-month FU. An impaired preprocedural 3D-RVEF <44% conferred higher mortality risk (Figure), and was an independent predictor for 1-year mortality (hazard ratio 5.32, p=0.033) in multivariable analysis. Tricuspid annular systolic excursion (TAPSE) and RV fractional area change were not predictive for this endpoint. Importantly, the observed decrease of 3D-RVEF function after TTVR was not associated with outcome (p=0.22 for decrease of 3D-RVEF vs. no decrease of 3D-RVEF in Kaplan-Meier analysis). Instead, left ventricular stroke volume index increased by 9.2% from 26.0 to 28.4 ml/m 2 (p<0.01) Conclusion: TTVR leads to right ventricular reverse remodeling and decrease of RV systolic function after TTVR. Impaired preprocedural RV systolic function is associated with worse clinical outcome. In contrast, the observed decrease of RV systolic function after TTVR was not associated with outcome. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Klinikum der Universtität München